Możliwości opieki logopedycznej w kontekście prowłączających działań i rozwiązań w systemie edukacji - Janiszewska-Nieścioruk, Zdzisława (Wydawnictwo Naukowe UAM, 2013)
Speech therapy, realized in the framework of a well-organized system, has a signifi cant meaning for the quality of promoting the inclusion of students with special needs in mainstream education. There is a need for guaranteed specialist support in the framework of a diversifi ed and extensive therapeutic offer as well as for highly trained professionals. In the case of inclusion, support is given by the cooperative team of specialists – teachers, educators, pedagogues, and speech therapists. The work of a team for a child/pupil should be a consequence of previously made decisions and actions, they should include the progress of education and effi ciency (or lack of it) of adopted forms of therapy or support. Long-term educational and therapeutic support, differentiated and yet more valid, because being under constant control and evaluation creates a new educational reality for children/pupils with special needs. A question might be stated whether the mainstream education system is designed in order to provide incessant and comprehensive support, especially as organized speech therapy care, and how this preparation should be understood. In the article I have attempted to present the possibilities of pro-inclusive changes in the education system as well as the weaknesses which might impede or limit this care.
Possibilities of Speech Therapy in the Context of Pro-Inclusive Activities and Solutions in the Education System
Keywords: speech therapy care; inclusion education; student with special needs